2016
DOI: 10.1371/journal.pone.0165769
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of PITX2 and PANCR Is Prognostic for Overall Survival in Patients with Resected Adenocarcinomas of the Biliary Tract

Abstract: Biliary tract cancers (BTC) are rare but highly aggressive malignant epithelial tumors. In order to improve the outcome in this lethal disease, novel biomarkers for diagnosis, prognosis, and therapy response prediction are urgently needed. DNA promoter methylation of PITX2 variants (PITX2ab, PITX2c) and intragenic methylation of the PITX2 adjacent non-coding RNA (PANCR) were investigated by methylations-specific qPCR assays in formalin-fixed paraffin-embedded tissue from 80 patients after resection for BTC. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…However, a retrospective study found that AREG gene body methylation levels are not as predictive as AREG mRNA levels and cannot yet be used as a clinically reliable biomarker, but they still provide an important clue for further research [ 124 ]. In addition, in patients with cholangiocarcinoma, patients with higher methylation levels of PITX2-adjacent noncoding RNAs had relatively longer survival and could be an independent prognostic factor [ 125 ] (Table 3 ).…”
Section: Gene Body Methylation and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, a retrospective study found that AREG gene body methylation levels are not as predictive as AREG mRNA levels and cannot yet be used as a clinically reliable biomarker, but they still provide an important clue for further research [ 124 ]. In addition, in patients with cholangiocarcinoma, patients with higher methylation levels of PITX2-adjacent noncoding RNAs had relatively longer survival and could be an independent prognostic factor [ 125 ] (Table 3 ).…”
Section: Gene Body Methylation and Cancermentioning
confidence: 99%
“…In addition, in patients with cholangiocarcinoma, patients with higher methylation levels of PITX2-adjacent noncoding RNAs had relatively longer survival and could be an independent prognostic factor [ 125 ] (Table 3 ).…”
Section: Gene Body Methylation and Cancermentioning
confidence: 99%
“…In recent years, PITX2 has attracted interest as a potential biomarker in malignant tumors, i.e. non-small cell lung cancer (NSCLC), biliary tract cancers, prostate cancer, and breast cancer [ 16 , 19 27 ]. In NSCLC, PITX2 hypermethylation was identified as significant predictor of progression-free survival [ 28 ].…”
Section: Introductionmentioning
confidence: 99%